Bioactive compounds from the African medicinal plant Cleistochlamys kirkii as resistance modifiers in bacteria. (21st February 2018) - Kincses, Annamária; Varga, Borisz; Csonka, Ákos; Sancha, Shirley; Mulhovo, Silva; Madureira, Ana Margarida; Ferreira, Maria‐José U.; Spengler, Gabriella
Abstract : Cleistochlamys kirkii (Benth) Oliv. (Annonaceae) is a medicinal plant traditionally used in Mozambique to treat infectious diseases. The aim of this study was to find resistance modifiers in C. kirkii for Gram‐positive and Gram‐negative model bacterial strains. One of the most important resistance mechanisms in bacteria is the efflux pump‐related multidrug resistance. Therefore, polycarpol (1 ), three C ‐benzylated flavanones (2 –4 ), and acetylmelodorinol (5 ) were evaluated for their multidrug resistance‐reverting activity on methicillin‐susceptible and methicillin‐resistant Staphylococcus aureus and Escherichia coli AG100 and AG100 A strains overexpressing and lacking the AcrAB–TolC efflux pump system. The combined effects of antibiotics and compounds (2 and4 ) were also assessed by using the checkerboard microdilution method in both S. aureus strains. The relative gene expression of the efflux pump genes was determined by real‐time reverse transcriptase quantitative polymerase chain reaction. The inhibition of quorum sensing was also investigated. The combined effect of the antibiotics and compound2 or4 on the methicillin‐sensitive S. aureus resulted in synergism. The most active compounds2 and4 increased the expression of the efflux pump genes. These results suggested that C. kirkii constituents could be effective adjuvants in the antibiotic treatment of infections.